Response of tomato plants to diesel fuel, gasoline and benzene - Morelos-Moreno, Alvaro; Martel-Valles, José Fernando; Morales-Díaz, América Berenice; Foroughbakhch-Pournavab, Rahim; Morales, Isidro; Benavides-Mendoza, Adalberto (REVISTA TERRA LATINOAMERICANA, 2019)
Oil and gas industry produces wastewater (produced water), which contains hydrocarbons, heavy metals, and other components, such as mineral salts essential for plant nutrition. Hydrocarbons presence on produced water limits its potential use in the agriculture, as its lead to inhibition of plant growth. The present study aimed to investigate the effect of hydrocarbons analogous contained in the produced water on 1) pH and electrical conductivity (EC) of irrigation leachate, 2) plant´s morphological variables, 3) mineral concentration, 4) fruit pH, EC and total dissolved solids (TDS), during flowering and fruiting stages in tomato grown into greenhouse conditions. As source of produced water were used diesel at concentrations of 20 and 25 mg L‑1, gasoline at 40, 50 and 60 mg L-1, and benzene at 75 mg L-1, applied in the substrate by means of a syringe. All plants treated with hydrocarbons reached the fruit setting and ripening stage at the 6-cluster. Depending on their type, concentration, and exposure time, hydrocarbons modif ied the pH and EC of the irrigation leachate, caused signif icant morphological changes with longer exposure time, and restricted the biomass production. Mineral concentration differed signif icantly among plant organs, affecting mainly the sodium uptake in stems and fruits. The variables of fruit quality, EC and TDS were favorably modif ied by most treatments.